2015
DOI: 10.1002/lary.25723
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of embouchure dysfunction: Experience of 139 patients at a single center

Abstract: 4. Laryngoscope, 126:1327-1333, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…There are no effective treatments for focal embouchure dystonia (FED). 6 A subset of affected individuals have progression of their symptoms to involve additional orofacial tasks, 5,6 but the risk factors for generalization remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no effective treatments for focal embouchure dystonia (FED). 6 A subset of affected individuals have progression of their symptoms to involve additional orofacial tasks, 5,6 but the risk factors for generalization remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia in brass musicians most commonly involves the embouchure, the positioning of orofacial muscles used to play a wind instrument. There are no effective treatments for focal embouchure dystonia (FED) . A subset of affected individuals have progression of their symptoms to involve additional orofacial tasks, but the risk factors for generalization remain unknown.…”
mentioning
confidence: 99%
“…In focal/segmental dystonia, medical treatment may have a primary role when BoNT is not technically feasible, or where BoNT is prone to side effects or functional impairment such as tongue or embouchure dystonia [188]. In general, location of dystonia does not impact the choice of medication.…”
Section: Reviewmentioning
confidence: 99%
“…To elucidate these issues, we examined patients with embouchure dystonia (ED) as an example of FTSD, using fMRI during both embouchure and somatotopy tasks. ED is a type of FTSD affecting the lip, jaw, tongue, facial, laryngeal, or masticatory muscles, such as involuntary tremor or lip‐pulling while controlling air flow into the mouthpiece of a wind instrument such as trombone, trumpet, or horn (Frucht, , ; Iltis et al, ; Termsarasab & Frucht, ). Previous imaging studies reported aberrant brain activity in sensorimotor areas while patients with ED blew into an MRI‐compatible mouthpiece (Haslinger et al, ).…”
Section: Introductionmentioning
confidence: 99%